Nutrition Protocol in General Care for Patients with Parkinson Disease - Ligia Maria Marcos Plasencia; Arnoldo Padrón Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The Illness of Parkinson (EP) is a process neurodegenerativo of sporadic presentation. It was described by James Parkinson in 1817. Of cause multifactorial, being the main factors etiológicos of genetic and environmental nature. Until the moment he/she only has palliative" "treatment by means of medications like the levodopa, which restores the levels of cerebral dopamina and they can improve the symptoms for a while. The symptoms non motors are as responsible direct factors of the poor quality of life of the patient parkinsonianos, varied, frequent and of undervalued impact. The sick persons are prone to the loss of weight and the malnutrition. The involuntary movements are in an expense of growing energy and the symptoms of the illness like the secondary effects of the treatment can limit the consumption of foods. It is necessary an integral attention to minimize their limitations and to improve this way their quality of life and that of their family. Inside an integral attention, the aspect of the feeding-nutrition is cardinal for what offers a work protocol here for the nutritional intervention to the sick person of Parkinson.﻿